2019
DOI: 10.1017/s1751731118001088
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal behaviors and herd characteristics of dairy cows housed in a compost-bedded pack barn system under hot and humid conditions

Abstract: With international demand for production systems aimed at thermal comfort and animal welfare, milk producers have become increasingly interested in compost barns. However, doubts about the behavioral aspects of cows in tropical and subtropical climates remain, because the compost barn system offers a larger bed area per animal at a lower stocking rate. The objective of this study was to evaluate whether the diurnal behaviors, hygiene and lameness of crossbred dairy cows are influenced by different number of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 26 publications
1
31
2
3
Order By: Relevance
“…Ouweltjes and Smolders (2014) also found more frequent positive interactions (allogrooming, or social licking) in herds housed in CBP than in other housing systems. Recently, Pilatti et al (2019) observed the social behavior of cows in CBP under hot and humid conditions. The multiparous cows exhibited significantly more pushing behavior than the primiparous cows, especially during the hottest hours of the day.…”
Section: Cow Behavior and Reproductive Performancementioning
confidence: 99%
“…Ouweltjes and Smolders (2014) also found more frequent positive interactions (allogrooming, or social licking) in herds housed in CBP than in other housing systems. Recently, Pilatti et al (2019) observed the social behavior of cows in CBP under hot and humid conditions. The multiparous cows exhibited significantly more pushing behavior than the primiparous cows, especially during the hottest hours of the day.…”
Section: Cow Behavior and Reproductive Performancementioning
confidence: 99%
“…In these regions during the hottest times of the day (maximums up to 35.9 °C and THI of 83 at 15h00), cows crowd into areas with mixing fans blowing on them and they are panting. This stress pattern may be trigger disputes over resources such as ventilation, water and space (Pilatti et al, 2018).…”
Section: Respiratory Rate and Skin Temperaturementioning
confidence: 99%
“…This finding may be related to the animals not being under direct solar radiation. Changes in room temperature affect body temperature, by increasing rectal temperature, respiratory rate, surface temperature, and activate thermoregulatory responses to maintain thermostability (Pilatti et al, 2018;Mota et al, 2019).…”
Section: Respiratory Rate and Skin Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The observations were performed by three trained observers, blinded to treatment, who alternated between each treatment on each new observation day. Behaviours were evaluated using a previously proposed ethogram [8,18], as described in Table 2. In addition, aiming a better understanding about the manure deposition from congregate in in possible better ventilated areas, we divided the barn in a grid of 18 quadrants uniformed distributed (Figure 1).…”
Section: Thi and Behaviour Recordingmentioning
confidence: 99%